The Great Masquerader: Tuberculosis Presenting as Community-Acquired Pneumonia - Dheda, Keertan; Makambwa, Edson; Esmail, Aliasgar (Seminars in Respiratory and Critical Care Medicine, 2020)
According to World Health Organization estimates, tuberculosis (TB) and lower respiratory tract infections (LRTIs) are both among the top 10 global causes of death. TB and community-acquired pneumonia (CAP), if mortality estimates are combined, would rank as the third most common cause of death globally. It is estimated that each year there are approximately 10 million new cases of TB that are associated with approximately 1.2 million deaths, and almost 450 million new episodes of LRTI (synonymous with CAP) with approximately 4 million associated deaths. Globally, Streptococcus pneumoniae remains the most common cause of CAP. However, although well documented, it is not widely appreciated that in several parts of the world, including sub-Saharan Africa, Asia, and South America, Mycobacterium tuberculosis is an important cause of CAP, if not the most common organism isolated in such settings. Thus, CAP due to M. tuberculosis is not uncommon in some parts of the world with up to a third of cases being attributable to M. tuberculosis. Consequently, TB remains an important clinical entity in the intensive care unit in these settings. Despite its frequency and importance, there are very limited data about TB CAP. In this review we discussed the epidemiology, immunopathogenesis, clinical presentation, diagnosis, management, prognosis, and prevention of TB CAP. The utility of newer diagnostic approaches is highlighted.
Keywords: tuberculosis; community-acquired pneumonia; lower respiratory tract infection; intensive care unit; critically ill